Impact of ozone-biologically active filtration on the breakthrough of Perfluoroalkyl acids during granular activated carbon treatment of municipal wastewater effluent. (1st September 2022) - Vatankhah, Hooman; Tajdini, Bahareh; Milstead, Reid P.; Clevenger, Erica; Murray, Conner; Knappe, Detlef; Remucal, Christina K.; Bellona, Christopher
Highlights: Performance of GAC for PFAA removal from wastewater effluent was investigated. Standalone O3 and BAF improved GAC performance compared to no-pretreatment. O3 -BAF in tandem improved PFAA removal by GAC compared to standalone O3 and BAF. Pore constriction/blockage may be the predominant mode of GAC fouling. Abstract: The presence of perfluoroalkyl acids (PFAAs) in municipal wastewater has highlighted the need to develop PFAA treatment approaches for wastewater effluent and potable reuse applications. Ozone (O3 ) and biologically active filtration (BAF) were investigated as standalone and combined pretreatment processes to improve the performance of granular activated carbon (GAC) for PFAA removal from wastewater effluent. As individual processes, ozonation at all three investigated doses (0.35, 0.75, 1.0 mg O3 /mg DOC) and BAF at both tested empty bed contact times (EBCT; 15 and 20 min) led to significant improvement in PFAA removal by subsequent GAC treatment. With respect to standalone ozonation, the specific O3 dose of 0.75 mg O3 /mg DOC was proven to be the optimum operating condition as further increase of the specific ozone dose to 1.0 mg O3 /mg DOC did not provide considerable additional improvement. Extending the EBCT during standalone BAF from 15 to 20 minutes significantly improved the efficacy of GAC for the removal of tested PFAAs. Pretreatment with O3 -BAF (0.75 mg O3 /mg DOC; 20 min EBCT) in tandem outperformed both standalone ozonation and BAF for the removal of PFAA by GAC. Characterization of effluent organic matter (EfOM) by size exclusion chromatography (SEC) and Fourier transform-ion cyclotron resonance mass spectrometry (FT-ICR-MS) before and after pretreatments suggest that among multiple co-occurring phenomena, the shift towards smaller and more polar EfOM may have predominantly alleviated pore constriction/blockage without having adverse impact on direct site competition. This observation is supported by SEC and FT-ICR-MS results indicating reduced EfOM molecular size through O3 and BAF pretreatment as well as transition to more hydrophilic byproducts. Graphical abstract: Image, graphical abstract